Correlation among some phenological and biochemical traits in date palm (Phoenix dactylifera L.) germplasm - Ahmad, Riaz; Ali, Hayssam M.; Lisek, Anna; Mosa, Walid F. A.; Ercisli, Sezai; Anjum, Muhammad Akbar (Frontiers in Plant Science, 2023)
Date palm is an economically important fruit crop of arid and semi-arid regions of the world. The knowledge on genetic variation, genotype-by-traits comparison, as well as relationship among several phenological traits is effective in developing breeding population through best allelic combinations and employing selection approaches. Information regarding the genetic variability and inter-relationship among fruit characters is facilitating the plant breeders to efficiently exploit the date palm germplasm for introduction of elite genotypes. Present study was conducted to examine genetic variation among different date palm cultivars collected from two different research stations of Pakistan as well as relationship among their phenological and biochemical characters. Biplot analysis revealed that the cultivars Dhakki, Chohara and Kupra possessed the highest fruit and pulp weights. Moreover, the fruits of the cultivars Champa Kali and Shakri had the maximum TSS (total soluble solids) and total sugars content. Similar variations were observed in mean values of the studied phenological and biochemical characters as in biplot analysis. Cluster analysis on the basis of phenological and biochemical characters divided 50 cultivars into seven clusters, showing differences in the studied characters. Correlation matrix revealed that pulp weight had strong relationship with fruit weight, length and diameter. Strong correlation also existed among antioxidant capacity, antioxidant activity and total phenolic content. These results demonstrated a huge diversity in phenological and biochemical characters as well as correlation among several characters of the studied germplasm, which can be exploited in future breeding programs.